A Comparative Analysis of Canadian University Policies Toward Alcohol, Drugs, and Gambling Use. Issue 1 (March 2018) - Marchica, Loredana; Zhao, Yaxi; Richard, Jeremie; Derevensky, Jeffrey; Shaffer, Howard J.
ABSTRACT: Objectives: Emerging adulthood remains a critical period in the participation of risky behaviors, including alcohol and substance use as well as gambling. College students are at greatest risk for participation in these risky behaviors because they are continuously exposed to multiple, drinking, substance use, and gambling environments without the support and guidance often present at home. Previous public policy studies have suggested that college and university policies might help decrease a variety of risky behaviors (eg, alcohol, substance use and gambling) among students. Although some studies have compared gambling-related policies to alcohol and substance use related policies in the United States, this has not yet been done in Canada. Thus, the current study constitutes the first Canadian comparison of college gambling policies to alcohol and substance use policies. Methods: Data were collected from 96 English and French colleges/universities across Canada adapting Shaffer et al's (2005) 15-item measure assessing the prevalence of gambling, alcohol and substance use related policies. Results: Analyses revealed significantly more schools had either an alcohol or substance use related policy (90% and 83%), compared to schools with a gambling-related policy (32%). Conclusions: The scarce prevalence of college gambling-related policies suggests that Canadian colleges and universities underestimate the risks associated with heavy participation in gambling activities. Although alcohol and substance use policies remain essential, gambling policies can have a significant influence on college student participatory behaviors. The present research suggests greater awareness and need for college and university administrators to develop appropriate gambling-related policies and programs.